Medida de la influencia de una propuesta de valor sustentable en empresas de retail: Caso: "multitiendas" de la Región de Coquimbo - Chile; Measurement of the influence of a sustainable value proposition in retail companies: Case: "multistores" in the Coquimbo Region - Chile - Segundo Ricardo Cabana Villca; Mauricio Israel Aguilera Zambra; Camila Constanza Ramírez Vega; Juan Carlos Antonio Rojas Godoy (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– In the global context related to the social and environmental crisis, this article aims to carry out an analysis of the variables that influence the competitiveness of multi-store companies in the Coquimbo Region, Chile, based on the formulation and effective use of a sustainable value proposition. A causal model composed of seven hypotheses is presented, with six study variables: sustainable value proposition (socio-environmental), customer loyalty, value co-creation, sustainable innovation, eco- efficiency and business competitiveness. The target population, through a representative sample of 383 people, are the consumers of the main regional retail stores. For the contrast of the proposed model, the method of structural equations is used, through Partial Least Squares (PLS). It is determined that the hypotheses raised are accepted and that the factors indicated explain the variance of business competitiveness by 89.9 %.
Keywords: C12; M14; O35; Q56; 330; Business competitiveness; sustainable value proposition; customer loyalty; value co; creation; sustainable innovation; eco; efficiency